Death and dying in prehospital care: what are the experiences and issues for prehospital practitioners, families and bystanders? A scoping review. Issue 9 (18th September 2020) - Myall, Michelle; Rowsell, Alison; Lund, Susi; Turnbull, Joanne; Arber, Mick; Crouch, Robert; Pocock, Helen; Deakin, Charles; Richardson, Alison
Abstract : Objective: To identify the factors that shape and characterise experiences of prehospital practitioners (PHPs), families and bystanders in the context of death and dying outside of the hospital environment where PHPs respond. Design: A scoping review using Arksey and O'Malley's five-stage framework. Papers were analysed using thematic analysis. Data sources: MEDLINE; Embase; CINAHL; Scopus; Social Sciences Citation Index (Web of Science), ProQuest Dissertations & Theses A&I (Proquest), Health Technology Assessment database; PsycINFO; Grey Literature Report and PapersFirst were searched from January 2000 to May 2019. Eligibility criteria for selecting studies: Qualitative and mixed methods studies reporting the experiences of PHPs, families and bystanders of death and dying in prehospital settings as a result of natural causes, trauma, suicide and homicide, >18 years of age, in Europe, USA, Canada, Australia and New Zealand. Results: Searches identified 15 352 papers of which 51 met the inclusion criteria. The review found substantial evidence of PHP experiences, except call handlers, and papers reporting family and bystander experiences were limited. PHP work was varied and complex, while confident in clinical work, they felt less equipped to deal with the emotion work, especially with an increasing role in palliative and end-of-life care. Families and bystanders reported generally positive experiences but their support needs were rarely explored. Conclusions: To the best of our knowledge this is the first review that explores the experiences of PHPs, families and bystanders. An important outcome is identifying current gaps in knowledge where further empirical research is needed. The paucity of evidence suggested by this review on call handlers, families and bystanders presents opportunities to investigate their experiences in greater depth. Further research to address the current knowledge gaps will be important to inform future policy and practice.